Management Category and Ecological Representativeness of the Conservation Units of the state of Ceará - Brazil - Ziegler, Henrique Ricardo Souza; Vidal de Oliveira, Vladia Pinto; Marinho, Jefferson Roberto de Oliveira (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
Considering the need to conserve the different ecosystems associated to the different Brazilian biomes, this work aims to analyze the conservation units of State of Ceará, having as parameters the different management categories and the ecological representativeness of the biomes of these areas. The polygons of the protected areas were analyzed, in addition to their creation decrees, provided by the Environment Department of the state of Ceará (SEMA). The predominant management group consisted of sustainable use, representing 62% in number and 55% in the total area of protected area in the state, being the Environmental Protection Area the most abundant category, with 15 areas, totaling 99.2% of the territorial extension of the area of protected of sustainable use and 56% of the number of conservation units. The Atlantic Forest presented a greater quantity and index of protected areas, with 21 areas covering about 6% of its territory in protected areas. On the other hand, in the Caatinga there are 4 protected areas that cover only 0.25% of its total territory. The Marine Biome has only one conservation unit, the less protected biome. In this sense, efforts are needed to increase the number of conservation units in Ceará, mainly in the Caatinga and Marinho biome.